GEOGRAPHIC INFORMATION SYSTEM (GIS) APPLICATION FOR MAPPING INFRASTRUCTURE AND TOURISM POTENTIAL IN MANSINAM VILLAGE - Karubaba, Andrew Federico; Kainama, Agus; Yemima, Hulda; Tinungki, Sheila Maria; Ainun, Annisa Nur; Behuku, Azazia; Dora, Syeli Patricia Cleo; Sabandar, Ofel Yakhin (INTAN Jurnal Penelitian Tambang, 2025)
This study aims to provide accurate spatial data to support ecotourism planning in Mansinam Village through the application of a Geographic Information System (GIS). Field data acquisition was conducted using a handheld GPS to record the coordinates of infrastructure and tourist attractions. The data was then processed in ArcGIS software through the stages of georeferencing, digitization, overlay analysis, and thematic map creation. This follows spatial mapping standards commonly used in geological mapping and spatial analysis activities in the mining sector. This study produced two thematic maps: a Settlement Map and a Map of Tourist Attraction Locations in Mansinam Village. Both maps provide spatial information on settlement locations, accessibility levels, and the distribution of natural, cultural, religious, and historical tourist attractions. The spatial analysis demonstrates the relationship between accessibility and tourism development potential, while also identifying locations requiring infrastructure improvements. In addition to contributing to tourism planning, the mapping process used also demonstrates methodological alignment with geological mapping and spatial analysis practices commonly used in the mining sector. The findings of this study are expected to provide an empirical basis for local governments and stakeholders in formulating more targeted and sustainable regional development strategies.